Toward high‐efficiency photovoltaics‐assisted electrochemical and photoelectrochemical CO2 reduction: Strategy and challenge - Jin Hyuk Cho; Joonhee Ma; Soo Young Kim (Exploration, 2023)
Abstract The realization of a complete techno‐economy through a significant carbon dioxide (CO2) reduction in the atmosphere has been explored to promote a low‐carbon economy in various ways. CO2 reduction reactions (CO2RRs) can be induced using sustainable energy, including electric and solar energy, using systems such as electrochemical (EC) CO2RR and photoelectrochemical (PEC) systems. This study summarizes various fabrication strategies for non‐noble metal, copper‐based, and metal–organic framework‐based catalysts with excellent Faradaic efficiency (FE) for target carbon compounds, and for noble metals with low overvoltage. Although EC and PEC systems achieve high energy conversion efficiency with excellent catalysts, they still require external power and lack complete bias–free operation. Therefore, photovoltaics, which can overcome the limitations of these systems, have been introduced. The utilization of silicon and perovskite‐based solar cells for photovoltaics‐assisted EC (PV‐EC) and photovoltaics‐assisted PEC (PV‐PEC) CO2RR systems are cost‐efficient, and the III–V semiconductor photoabsorbers achieved high solar‐to‐carbon efficiency. This work focuses on PV‐EC and PV‐PEC CO2RR systems and their components and then summarizes the special cell configurations, including the tandem and stacked structures. Additionally, the study discusses current issues, such as low energy conversion, expensive PV, theoretical limits, and industrial scale–up, along with proposed solutions.